This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How did = A 3 + B 3 + 3 ( A + B ) Turn to = A 3 + B 3 + 3 A B S ?
Let x = ( 2 + 5 ) 3 1 + ( 2 − 5 ) 3 1 ⟹ x − ( 2 + 5 ) 3 1 − ( 2 − 5 ) 3 1 = 0
So we have x 3 − ( 2 + 5 ) − ( 2 − 5 ) = 3 x ( 2 2 − 5 ) 3 1 ⟹ x 3 + 3 x − 4 = 0 , Since x = 1 is a root of the equation and the other roots are non-real as x 2 + x + 4 = 0 has no real solutions it follows that 1 = ( 2 + 5 ) 3 1 + ( 2 − 5 ) 3 1
Since integer solution is expected, we can assume 2 ± 5 = ( a ± b 5 ) 3 , then we have 3 2 + 5 + 3 2 − 5 = 3 ( a + b 5 ) 3 + 3 ( a − b 5 ) 3 = a + b 5 + a − b 5 = 2 a . We have:
( a + b 5 ) 3 a 3 + 3 a 2 b 5 + 1 5 a b 2 + 5 b 3 5 = 2 + 5 = 2 + 5
Equating the rational and irrational parts we have: { a 3 + 1 5 a b 2 = 2 3 a 2 b + 5 b 3 = 1 ⟹ a = b = 2 1 .
⟹ 3 2 + 5 + 3 2 − 5 = 2 a = 2 × 2 1 = 1
Problem Loading...
Note Loading...
Set Loading...
Let A = 3 2 + 5 , B = 3 2 − 5 .
And, ⇒ S = A + B = 3 2 + 5 + 3 2 − 5
Now, Cubing both sides.
⇒ S 3 = ( A + B ) 3
= A 3 + B 3 + 3 A B ( A + B )
= A 3 + B 3 + 3 A B S ...... ( ♧ ) [ Since , ( A + B ) = S ]
Thus,
⇒ A 3 + B 3 = ( 3 2 + 5 ) 3 + ( 3 2 − 5 ) 3
= 2 + 5 + 2 − 5
= 4
⇒ 3 A B = 3 ( 3 2 + 5 ) ( 3 2 − 5 )
= 3 ( 3 4 − 5 )
= 3 ( 3 − 1 )
= 3 × ( − 1 )
= − 3
Now, putting ( A 3 + B 3 ) = 4 and ( 3 A B ) = − 3 in ( ♧ ) .
⇒ S 3 = 4 − 3 S
S 3 + 3 S − 4 = 0
( S − 1 ) ( S 2 + S + 4 ) = 0
S − 1 = 0
S = 1
⇒ 3 2 + 5 + 3 2 − 5 = 1 .
Note : There is a possibilty that ( S 2 + S + 4 = 0 ) ,but this is not possible because its roots are non-real complex numbers.And the surds given is real.